Mutation analysis of the 2 kb 5' to SRY in XY females and XY intersex subjects. Issue 6 (June 1996) - Kwok, C; Tyler-Smith, C; Mendonca, B B; Hughes, I; Berkovitz, G D; Goodfellow, P N; Hawkins, J R
Abstract : Mutations in the Y linked testis determining gene SRY cause 46, XY sex reversal. However, only about 15% of cases of 46, XY sex reversal are accounted for by mutations in SRY. In this study we have investigated the possibility that mutations affecting the expression of SRY might cause some of the cases of sex reversal in which the coding sequence of SRY is normal. We have screened 2 kb of DNA immediately 5' to the SRY coding sequence in 49 subjects with varying degrees of 46, XY sex reversal. Two variant bases were identified, one of which was determined to be a polymorphism and the other is unique, but familial.